Daytime sleepiness: more than just Obstructive Sleep Apnea (OSA) - Ferini-Strambi, Luigi; Sforza, Marco; Poletti, Mattia; Giarrusso, Federica; Galbiati, Andrea (La Medicina del Lavoro, 2017)
Excessive Daytime Sleepiness (EDS) is a common condition with a significant impact on quality of life and general health. A mild form of sleepiness can be associated with reduced reactivity and modest distractibility symptoms, but more severe symptomatic forms are characterized by an overwhelming and uncontrollable need to sleep, causing sudden sleep attacks, amnesia and automatic behaviors. The prevalence in the general population is between 10 and 25%. Furthermore, EDS has been considered a core symptom of obstructive sleep apnea (OSA), as well as being the main symptom of primary hypersomnias such as narcolepsy types 1 and 2, and idiopathic hypersomnia. Moreover, it can be considered secondary to other sleep disorders (Restless Legs Syndrome, Chronic insomnia, Periodic Limb Movements), psychiatric conditions (Depression, Bipolar Disorder) or a consequence of the intake/abuse of drugs and/or substances. An accurate medical history cannot be sufficient for the differential diagnosis, therefore instrumental recordings by means of polysomnography and the Multiple Sleep Latency Test (MSLT) are mandatory for a correct diagnosis and treatment of the underlying cause of EDS.